MINAT MAHASISWA BERINVESTASI DI PASAR MODAL DITINJAU DARI PENGETAHUAN DAN MOTIVASI - Tohari, Dede; Atieq, Muhammad Qoes (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The existence of the Indonesian Stock Exchange Sharia Investment Gallery in universities is expected to provide education from an early age about investing in the Islamic capital market and become an intermediary towards mastering science and its practice in the capital market to the academic world, but in fact the interest of academics, including students, to invest is relatively low as seen from the current number of investors, there are only 248 students out of a total of 2.939 FSEI students. Therefore, this research is motivated by the low number of investors from among students who have become customers and actively invest in GIS BEI IAIN Syekh Nurjati Cirebon. This study uses quantitative methods with a total sample of 97 respondents. The results showed that investment knowledge partially has a positive and significant effect on student interest in investing in the Islamic capital market at GIS BEI IAIN Syekh Nurjati Cirebon. While investment motivation partially does not have a positive and significant effect on students' interest in investing in the Islamic capital market at GIS BEI IAIN Syekh Nurjati Cirebon and simultaneously investment knowledge and investment motivation have a positive and significant influence on student interest in investing in the Islamic capital market at GIS BEI IAIN Syekh Nurjati Cirebon